ANALYSIS OF MSME CREATIVE INDUSTRY IN PLASTIC WASTE RECYCLING IN SIDOKERTOTO VILLAGE, SIDOARJO REGENCY - Pramita Studiviany S; Ida Ayu Nuh Kartini; Muhammad Yasin (Jurnal Ekonomi, 2022)
The purpose of this study was to determine the condition of the UMKM Creative Industry in Plastic Waste Management in Sidokerto Village, Sidoarjo Regency and to analyze the development of the MSME Creative Industry in managing Plastic Waste in Sidokerto Village, Sidoarjo Regency. researchers used a field survey research design with a qualitative descriptive approach with MSME Creative Industry actors in Waste Management in Sidokerto Village, Sidoarjo Regency as samples in this study. The results of the study concluded that the condition of the MSME Creative Industry for Plastic Waste Management in Sidokerto Village, Sidoarjo Regency was supported by a waste bank as a provider of raw materials for waste management. The development of MSME creative industries for Plastic Waste Management in Sidokerto Village, Sidoarjo Regency can be carried out with a strong synergy between backward linkages, namely consistently implementing waste bank activities. Then, in the position of the creative industry, financial management, product quality, and technology use are further strengthened so that the resulting product strengths. In addition, future linkages in the form of expanding relations between distributors also need to expand marketing.